A note on the comparison of humpback whale tail fluke catalogues from the Sultanate of Oman with Madagascar and the East African mainland - Minton, G.; Cerchio, S.; Collins, T.; Ersts, P.; Findlay , K. P.; Pomilla , C.; Bennet , D.; Meyer , M. A.; Razafindrakoto, Y.; Kotze , P. G. H.; Oosthuizen , W. H.; Leslie , M.; et al. (J. Cetacean Res. Manage., 2023)
The photo-identification catalogue of humpback whale tail flukes from Oman was compared with those from Antongil Bay, Madagascar and study sites in South Africa and Mozambique collectively termed the ‘East African Mainland’. No matches were found, supporting other lines of evidence that the humpback whales studied off the coast of Oman form part of a discrete Arabian Sea population, which adheres to a Northern Hemisphere breeding cycle, and has little or no ongoing exchange with the nearest neighbouring populations in the southern Indian Ocean. While the sample size from Oman is small, and low levels of ongoing exchange might not be detected in this type of catalogue comparison, the study nonetheless emphasises the need to pursue research and conservation efforts in the known and suspected range of the Endangered Arabian Sea humpback whale population.